2005
DOI: 10.1038/nature03880
|View full text |Cite
|
Sign up to set email alerts
|

Young organic matter as a source of carbon dioxide outgassing from Amazonian rivers

Abstract: Amazonian river system. We find that respiration of contemporary organic 2 matter (less than 5 years old) originating on land and near rivers is the dominant source of excess carbon dioxide that drives outgassing in mid-size to large rivers, although we find that bulk organic carbon fractions transported by these rivers range from tens to thousands of years in age. We therefore suggest that a small, rapidly cycling pool of organic carbon is responsible for the large carbon fluxes from land to water to atmosphe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

27
563
6
7

Year Published

2007
2007
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 566 publications
(603 citation statements)
references
References 25 publications
27
563
6
7
Order By: Relevance
“…14 rivers has previously been undertaken using one of two methods: (1) an indirect method 63 whereby water samples are collected in the field, returned to the laboratory and the entire DIC 64 recovered as CO 2 by "gas-stripping" (e.g. Mayorga et al, 2005), or (2) a direct method 65 whereby CO 2 evading from the water surface is captured using a floating chamber and 66 adsorbed onto a molecular sieve, which can be subsequently processed in the laboratory to 67 recover the CO 2 for isotope analysis (Billett et al, 2006;Billett and Garnett, 2010).…”
mentioning
confidence: 99%
“…14 rivers has previously been undertaken using one of two methods: (1) an indirect method 63 whereby water samples are collected in the field, returned to the laboratory and the entire DIC 64 recovered as CO 2 by "gas-stripping" (e.g. Mayorga et al, 2005), or (2) a direct method 65 whereby CO 2 evading from the water surface is captured using a floating chamber and 66 adsorbed onto a molecular sieve, which can be subsequently processed in the laboratory to 67 recover the CO 2 for isotope analysis (Billett et al, 2006;Billett and Garnett, 2010).…”
mentioning
confidence: 99%
“…Various studies have been conducted to explore the fate of the SOC exported from the catchment: for instance, labile young organic matter delivered to river systems was found to be rapidly mineralised in the channel (e.g. Raymond and Bauer, 2001;Mayorga et al, 2005), while SOC reaching lakes and oceans has been shown to be well preserved over longer timescales (e.g. Rosen and Hammarlund, 2007;Galy et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…However, it could be more significant at other sites where the CO 2 degassed from the stream surface is more 14 C-depleted. For example, Mayorga et al (2005) observed 14 CO 2 concentrations in Amazonian rivers as low as ~25% Modern. In addition, at some sites the proportion of plant carbon being derived from evasion might be greater due to higher evasion rates, lower wind speeds, and different stream bank morphology.…”
Section: Discussionmentioning
confidence: 99%
“…This recently developed method allows direct collection of the evaded CO 2 and is considered preferable to previously used indirect methods (e.g. Mayorga et al 2005). …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation